Low Temperature-Induced 30 (LTI30) positively regulates drought stress resistance in Arabidopsis: effect on abscisic acid sensitivity and hydrogen peroxide accumulation - Shi, Haitao; Chen, Yinhua; Qian, Yongqiang; Chan, Zhulong (Frontiers in Plant Science, 2015)
As a dehydrin belonging to group II late embryogenesis abundant protein (LEA) family, Arabidopsis Low Temperature-Induced 30 (LTI30)/XERO2 has been shown to be involved in plant freezing stress resistance. However, the other roles of AtLTI30 remain unknown. In this study, we found that the expression of AtLTI30 was largely induced by drought stress and abscisic acid (ABA) treatments. Thereafter, AtLTI30 knockout mutants and overexpressing plants were isolated to investigate the possible involvement of AtLTI30 in ABA and drought stress responses. AtLTI30 knockout mutants were less sensitive to ABA-mediated seed germination, while AtLTI30 overexpressing plants were more sensitive to ABA compared with wild type (WT). Consistently, the AtLTI30 knockout mutants displayed decreased drought stress resistance, while the AtLTI30 overexpressing plants showed improved drought stress resistance compared with WT, as evidenced by a higher survival rate and lower leaf water loss than WT after drought stress. Moreover, manipulation of AtLTI30 expression positively regulated the activities of catalases (CATs) and endogenous proline content, as a result, negatively regulated drought stress-triggered hydrogen peroxide (H2O2) accumulation. All these results indicate that AtLTI30 is a positive regulator of plant drought stress resistance, partially through the modulation of ABA sensitivity, H2O2 and proline accumulation.